Analysis Using Of Different Liquids of the Bakpao Quality - Rizqullah, Adib Rifqi; Elida, Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
The use of various liquids in the making of buns inspired this study, which attempts to investigate the changes in bun quality caused by the use of various liquids. The addition of water to the dough prior to fermentation can have an impact on the fermentation process. The usage of young coconut water is one of the liquids that can alter the fermentation process. This study is a pure experiment with three repeats of a completely randomized design approach (CRD). The data was acquired directly from 5 expert panelists who answered a questionnaire (organoleptic test format) on the quality of the meatballs with the use of different liquids, then collated into tabular form and evaluated with the T (t) test to see the difference between the two treatments. If the data analysis reveals a t arithmetic t table, Ha is acceptable; if the data analysis reveals a t arithmetic t table, Ho is approved. Based on the findings of the data analysis of the buns using various liquids, it was determined that there was no significant difference in the quality of the buns between the X₁ and X₂ treatments, indicating that Ho was accepted. Overall, the greatest results from the two factors were discovered in buns with water use (X1) using the average tabulation of the data. Water (X₁) buns are preferred for further investigation because their shape, color, aroma, and texture are superior to that of young coconut water (X₂).